(untitled) (SETARA : Jurnal Ilmu Hukum, 2024)
This article examines the legal execution of court orders concerning the seizure of property connected to money laundering offences. The issue is important because asset seizure in money laundering cases stands at the intersection of criminal procedure, confiscation policy, and the broader goal of restoring illicit proceeds for the benefit of the public. Using normative juridical research, the article reviews Indonesian anti-money laundering law, criminal procedure rules, and judicial reasoning in Supreme Court Decision Number 1208K/Pid.Sus/2018. The study finds that the legal handling of seized assets remains problematic when courts rely on approaches that do not clearly distinguish between assets to be returned, assets to be forfeited to the state, and assets that should be tied to predicate offences and illicit proceeds. The article also finds that the case examined contains elements of predicate fraud and money laundering, raising the need for a more coherent asset-recovery framework. It concludes that legal certainty in this field depends on clearer statutory guidance, including the enactment of a more comprehensive asset forfeiture regime.